Emotional regulation as a transdiagnostic category through clinical problems: a narrative study - Paredes-Rivera, Alvaro (2021)
Background: In the diagnostic process of psychological disorders, we can find common characteristics to different problems, being able to explain a variety of clinical difficulties and comorbidities from this cross-sectional category, which has been called transdiagnostic. Being emotional regulation a transdiagnostic variable that is defined as the ability of the person to make use of resources or skills to modulate the behavioral response produced after experiencing a moderate to high intensity emotion. Objective: To explain the impact of the emotional regulation variable in clinical theory and practice through a transdiagnostic look. Discussion: The term transdiagnosis arises from a series of drawbacks in its foundation and practice, being these: dissatisfaction with traditional models such as the International Classification of Diseases and Disorders related to Mental Health (ICD-10) and Diagnostic and Statistical Manual of Mental Disorders (DSM-5), comorbidity and the risk of medicalization. For this reason, this model proposes to understand the common basic causal processes between different disorders or groups of these. To touch on the subject of emotional regulation, one must talk about emotions. These are adaptive for people. However, they can become problematic if they respond automatically under the emotional level, since it interferes with goals and personal well-being. All human beings have emotion regulatory processes, that is, we are capable of deciding how to respond to the appearance of an emotion. This is called emotional regulation (ER), which becomes effective when the context and long-term goals are adapted. This way of responding is a personal learned product that depends on the contingencies and the rules that the verbal community of reference has organized throughout personal history; so, at times, it can be destructive insofar as its rigid and often avoidant application prevents a person from building a meaningful life. Recent research shows that a significant number of clinical diagnoses in mental health could be explained by problems in emotional regulation, among which we have highlighted anxiety and depressive disorders, borderline personality disorder, and substance use disorders. and eating disorders. Conclusion: Transdiagnostic processes are increasingly valued due to the various explanatory theories that appear in recent years. Generating treatments focused on the deficit of skills in emotional regulation, all in order to improve the quality of life of the consultants. It should be added that when reviewing all this literature we can conclude that it is possible to conceptualize and explain psychological disorders from the deficit of emotional regulation. Especially from the biological and contextual points and taking into account the learning for its maintenance.